50th Jubilee Winter School on Wave and Quantum Acoustics XLIXth Winter School on Environmental Acoustics and Vibroacoustics Szczyrk, Poland, 28 February – 3/4 March, 2022 - WITOS, Franciszek (Archives of Acoustics, 2022)
There is no abstract.